PENINGKATAN EFISIENSI PROSES PRODUKSI KERAJINAN BAMBU MENGGUNAKAN MESIN PENGERING DI "TUNGGAK SEMI" BAMBOO HANDYCRAFT - Padmaningrum, Regina Tutik; Wijanarka, Bernadus Sentot; Hariyanto, V. Lilik (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
The purpose of this article is to discuss the production efficiency of making bamboo handicraft product by using dryer. The dryer as a tool that can overcome this problems are discussed starting from assembly, specifications, operating guidelines, and test try. Planned dryer basically consists of the heating room and heating units. Heating room made of masonry walls plastered with cement on the outside and inside of the room walls. There are two door to enter the heat product. Two glass window, which serve as monitors heating conditions. Two thermometers was placed on glass window. Result dryer manufacture process has been tested with results as follows: has created a dryer the size of the heating room 3 m x 6 m x 2.25 m, a wall of brick covered with cement, and the ceiling is made of asbestos. Heating unit has dimensions of 40 cm x 40 cm x 60 cm. Heating unit is heated by LPG gas stoves. The results show that a heating unit capable of heating the room temperature from 30oC to 40oC in 10 minutes. The water content of dried products decreased from 17.1% to about 2.5%. The capacity of the dryer is 300 products. The cost for drying the product is Rp47.33, - per product